Zwitterionic AIEgens: Rational Molecular Design for NIR‐II Fluorescence Imaging‐Guided Synergistic Phototherapy. (6th October 2020) - Zhu, Wei; Kang, Miaomiao; Wu, Qian; Zhang, Zhijun; Wu, Yi; Li, Chunbin; Li, Kai; Wang, Lei; Wang, Dong; Tang, Ben Zhong
Abstract: Fluorescence imaging in the second near‐infrared region (NIR‐II) can penetrate tissue at centimeter depths and obtain high image fidelity. However, facile synthesis of small‐molecule fluorescent photosensitizers for efficient NIR‐II fluorescence imaging as well as photodynamic and photothermal combinatorial therapies is still a challenging task. Herein, a rational design and facile synthesis protocol are reported for a series of novel NIR‐emissive zwitterionic luminogens with aggregation‐induced emission (AIE) features for cancer phototheranostics. Consistent with the intrinsic features including long emission wavelength, effective reactive oxygen species generation, and excellent photothermal conversion efficiency (35.76%), in vitro and in vivo evaluation show that one of these presented AIE luminogens provides excellent performance in NIR‐II fluorescence imaging‐guided synergistic phototherapy against cancer. Abstract : A series of NIR (near‐infrared)‐emissive zwitterionic AIEgens are rationally designed and facilely constructed for the first time. One of these AIEgens exhibits long emission wavelength, effective ROS generation, and high photothermal conversion efficiency, endowing it with excellent performance in NIR‐II fluorescence imaging‐guided synergistic photodynamic and photothermal combinatorial therapies.